Проблеми термінологічного розмежування понять “префікс” та “преверб” - Якубовська, H. (Вип. 11–12, Ч. 2, 2016)
В статті розглядається теоретична проблема розмежування термінологічних понять “префікс” і “преверб” у дослідженнях європейських мов, а також окреслюються особливості процесу превербації. Специфічний статус превербів, які в залежності від синтаксичної структури мови можуть займати препозиційне або постпозиційне положення, зумовлюється їхньою здатністю впливати як на семантику вербатива, так і на його актанти. Типологічні зіставлення превербів різних мовних груп виявляють їхні функційні відмінності: домінування функції Aktionsart у східних індоєвропейських мовах та синтаксичної – у західноєвропейських. The article deals with the theoretical problem of terminological distinction between the notions of “prefix” and “preverb” in the study of European languages and outlines specific features of preverbation process. The need to determine the terminological system in the domain of verbal derivation in European languages is particularly relevant and up-to-date in the process of comparative study of Slavic, Germanic and Romance languages. Structural composition of preverbs and verbs in some languages depends on many factors: semantic, pragmatic, stylistic, geographical, syntactic and prosodic. These structural features of language systems determine various approaches to the definitions and terminology designation of these language units. Typological comparison of languages demonstrates the division of preverb functioning in different language groups. In particular, the Aktionsart preverb function is predominant in the Eastern Indo-European languages, while in the Western European languages this function is primarily syntactic. In such languages as French, German and English, preverbs have special characteristic features i.e., preverb in French and German, postverb in the English language. Significant difference in quantitative, qualitative and functional composition of postpositional morphemes that are compatible with various lexical and grammatical classes of words provides grounds for the corresponding allocation of Ukrainian verb prefixes into a separate kind of morpheme, that is preverb. The need for assigning a special status to preverbal morphological units is determined by the difference between its functional role and the role of simple prefix, taking into account that preverb affects not only the verbal unit, but also its actants. Moreover, unlike the prefixes that The article deals with the theoretical problem of terminological distinction between the notions of “prefix” and “preverb” in the study of European languages and outlines specific features of preverbation process. The need to determine the terminological system in the domain of verbal derivation in European languages is particularly relevant and up-to-date in the process of comparative study of Slavic, Germanic and Romance languages. Structural composition of preverbs and verbs in some languages depends on many factors: semantic, pragmatic, stylistic, geographical, syntactic and prosodic. These structural features of language systems determine various approaches to the definitions and terminology designation of these language units. Typological comparison of languages demonstrates the division of preverb functioning in different language groups. In particular, the Aktionsart preverb function is predominant in the Eastern Indo-European languages, while in the Western European languages this function is primarily syntactic. In such languages as French, German and English, preverbs have special characteristic features i.e., preverb in French and German, postverb in the English language. Significant difference in quantitative, qualitative and functional composition of postpositional morphemes that are compatible with various lexical and grammatical classes of words provides grounds for the corresponding allocation of Ukrainian verb prefixes into a separate kind of morpheme, that is preverb. The need for assigning a special status to preverbal morphological units is determined by the difference between its functional role and the role of simple prefix, taking into account that preverb affects not only the verbal unit, but also its actants. Moreover, unlike the prefixes that are inseparable prepositive elements of a word, preverbs can be either separable or non-separable solid prepositive and postpositional elements. Keywords: preverb, prefix, prepositional morpheme, preverbation, particle, verbal stem, actant.
Yakubovska N. The problems of terminological demarcation between the notions of “prefix” and “preverb”
Keywords: преверб; префікс; препозиційна морфема; превербація; частка; дієслівна основа; актант